The mom inventors handbook : - Monosoff, Tamara (McGraw-Hill, 2005)
The Mom Inventors Handbook. gives practical step-by- step advice for putting inspiration into action. The book takes inventors from idea development to marketing and sales covering everything from market research to prototype development, manufacturing and licensing and debunks some common myths. It simplifies the invention process; even providing stories from real mom inventors sharing their 'aha' moments and lessons learned.